2010
DOI: 10.1053/j.gastro.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Study the Phenotypic Changes of Interstitial Cells of Cajal in Gastrointestinal Diseases

Abstract: BACKGROUND & AIMS Interstitial cells of Cajal (ICC) express the receptor tyrosine kinase, KIT, the receptor for stem cell factor. In the gastrointestinal (GI) tract, ICC are pacemaker cells that generate spontaneous electrical slow waves, and mediate inputs from motor neurons. Absence or loss of ICC are associated with GI motility disorders, including those consequent of diabetes. Studies of ICC have been hampered by the low density of these cells and difficulties in recognizing these cells in cell dispersions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 43 publications
1
69
0
Order By: Relevance
“…CopGFP-labeled cells within jejunal smooth muscle layers were identified by confocal microscopy (Fig 1A), and these cells were confirmed to be Kit + ICC by immunohistochemical labeling with KIT antibodies (Fig 1B), as previously reported [13]. ICC within the plane of the myenteric plexus (ICC-MY) and the deep muscular plexus (ICC-DMP) were labeled by copGFP (labeling of cytoplasm) and KIT antibodies (labeling of plasma membrane) (Fig 1C).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…CopGFP-labeled cells within jejunal smooth muscle layers were identified by confocal microscopy (Fig 1A), and these cells were confirmed to be Kit + ICC by immunohistochemical labeling with KIT antibodies (Fig 1B), as previously reported [13]. ICC within the plane of the myenteric plexus (ICC-MY) and the deep muscular plexus (ICC-DMP) were labeled by copGFP (labeling of cytoplasm) and KIT antibodies (labeling of plasma membrane) (Fig 1C).…”
Section: Resultssupporting
confidence: 84%
“…RT-PCR and qPCR analyses of cDNA were performed as previously described [13, 18]. All primers used for RT-PCR and qPCR are shown in S11 Table.…”
Section: Methodsmentioning
confidence: 99%
“…Kit +/copGFP (B6.129S7- Kit tm1Rosay /J) mice expressing copepod green fluorescent protein (copGFP) from the endogenous Kit locus, 21 Pdgfra +/eGFP (B6.129S4- Pdgfra tm11(EGFP)Sor /J) mice expressing histone H2B-enhanced GFP (eGFP) fusion protein from the endogenous Pdgfra locus 22 and strain-matched wild-type mice were from The Jackson Laboratory (Bar Harbor, ME). C57BL/6J, WBB6F1/J, WCB6F1/J and NOD/ShiLtJ mice 8 were also from The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…It was previously shown that knock-down of the Kit gene results in defective progenitor cell activity in many tissues 1922 . Indeed, hearts from Kit w/wv mice showed a dramatic reduction in resident mononuclear c-kit + cells and progenitor activity 23 .…”
Section: Kit-cre Locus Is Not Ectopically Inducedmentioning
confidence: 99%